2012
DOI: 10.1097/inf.0b013e31825ba6cf
|View full text |Cite
|
Sign up to set email alerts
|

Leukoreduction in Patients With Severe Pertussis With Hyperleukocytosis

Abstract: When pertussis is associated with hyperleukocytosis, mortality approaches to 80%. Immature leukocytes have been identified in pulmonary arterioles, small arteries and venules. Techniques aimed at reducing leukocyte mass might improve the prognosis of these patients. We report our experience with 3 patients in whom a leukoreduction was performed in the context of severe pertussis and hyperleukocytosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 14 publications
0
20
0
4
Order By: Relevance
“…Rowlands et al found that addition of leukodepletion by exchange transfusion in the intensive care of infants with critical pertussis reduced the mortality rate from 44% to 10% (Rowlands et al 2010). Additionally, there have been similar reports of cases where single or double volume exchange transfusion was successful in reducing leukocytosis and improving the outcome for infants with severe pertussis disease (Rowlands et al 2010;Martinez et al 2011;Lashkari, Karuppaswamy and Khalifa 2012;Onoro et al 2012;Berger et al 2013;Kuperman et al 2014). One of these cases also reported the beneficial effects of hyperhydration as a treatment for the leukocytosis (Lashkari, Karuppaswamy and Khalifa 2012), while another report found that leukopheresis as a method of leukodepletion was not effective in preventing death (Onoro et al 2012).…”
Section: Treatmentsmentioning
confidence: 80%
See 1 more Smart Citation
“…Rowlands et al found that addition of leukodepletion by exchange transfusion in the intensive care of infants with critical pertussis reduced the mortality rate from 44% to 10% (Rowlands et al 2010). Additionally, there have been similar reports of cases where single or double volume exchange transfusion was successful in reducing leukocytosis and improving the outcome for infants with severe pertussis disease (Rowlands et al 2010;Martinez et al 2011;Lashkari, Karuppaswamy and Khalifa 2012;Onoro et al 2012;Berger et al 2013;Kuperman et al 2014). One of these cases also reported the beneficial effects of hyperhydration as a treatment for the leukocytosis (Lashkari, Karuppaswamy and Khalifa 2012), while another report found that leukopheresis as a method of leukodepletion was not effective in preventing death (Onoro et al 2012).…”
Section: Treatmentsmentioning
confidence: 80%
“…Additionally, there have been similar reports of cases where single or double volume exchange transfusion was successful in reducing leukocytosis and improving the outcome for infants with severe pertussis disease (Rowlands et al 2010;Martinez et al 2011;Lashkari, Karuppaswamy and Khalifa 2012;Onoro et al 2012;Berger et al 2013;Kuperman et al 2014). One of these cases also reported the beneficial effects of hyperhydration as a treatment for the leukocytosis (Lashkari, Karuppaswamy and Khalifa 2012), while another report found that leukopheresis as a method of leukodepletion was not effective in preventing death (Onoro et al 2012). Assy et al de-scribed the use of leukofiltration using a leukocyte filter during ECMO in the successful treatment of an infant (Assy et al 2015).…”
Section: Treatmentsmentioning
confidence: 90%
“…L'utilisation de techniques d'échanges transfusionnels pour réduire l'hyperleucocytose majeure a été initialement décrite pour le traitement de la leucostase associée aux leucémies aiguës. La déplétion spécifique des leucocytes par leucocytaphérèse automatisée est la solution de choix mais elle nécessite un matériel spécifique peu disponible et une anticoagulation du circuit qui est susceptible d'induire des troubles de l'hémostase chez l'enfant de faible poids [8]. Cependant, la leucocytaphérèse est une option intéressante chez l'enfant déjà sous assistance extra-corporelle [9,10].…”
Section: Discussionunclassified
“…Les complications associées à la transfusion massive chez ces patients en HTAP comme l'hypothermie et l'hyperviscosité, illustrées par notre cas clinique, pourraient être limitées par le réchauffement du sang avant son administration, la reconstitution avec un taux d'hématocrite plus faible à 35 % en l'absence d'anémie ou la réalisation de 2 échanges simple volume à quelques heures d'intervalle. Plusieurs études de faibles niveaux de preuve ont rapporté un lien chronologique entre la réalisation de l'échange transfusionnel, la réduction de l'hyperleucocytose et l'amélio-ration clinique de l'enfant, argumentant pour une imputabilité possible (tableau I) [7][8][9][10][11][12][13][14][15][16][17]. Le succès de l'échange semblait dépendre de la sévérité clinique de l'enfant au moment de la réalisation de celui-ci.…”
Section: Discussionunclassified
“…27 reporta un caso de exanguinotransfusión con evolución favorable, y Oñoro y cols., 28 publican una serie de 3 casos sometidos a leucodepleción, 2 mediante exanguinotransfusión y el tercero por leucoféresis, con una supervivencia del 66%.…”
Section: Si Evoluciona Con Hipertensión Pulmonarunclassified